Labour Law Aspects of Child Labour in the Information Age - Tancer Verboten, Mojca (Children's Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges: Exploring Opportunities and Challenges, 2025)
The article analyses the labour law aspects of child labour in the information age. It presents in detail the specific features related to the regulation of child labour and the possibilities of applying labour law legislation particularly to the work of children under the age of 15, pupils and students. Three sections are discussed: the normative regulation of child labour, the specific features of performing light work by children, the special protection provisions that apply to child labour, and the specific features related to digital child labour, which is emerging as a new form of work. The basic hypothesis in the article is that when defining child labour and the emergence of new forms of work, such as the work of information child influencers, it is necessary to regulate this appropriately in a way that takes into account the specific features of the situation of children who perform such work so that such work does not harm their safety, health, morality, education and development.